New drugs for asthma - Barnes, Peter (Henry Stewart Talks, 2011)
Improvements in existing therapies have been the main approach, New classes of drug in development, Upcoming oral and inhaled therapies that target inflammation in asthma, Patients with severe disease, Inflammation in severe asthma is usually corticosteroid insensitive
Archived at 2021/09/29